1995
DOI: 10.2486/indhealth.33.67
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Study on Mortality among Japanese Coal Miners.

Abstract: We conducted a prospective study to clarify mortality patterns among Japanese coal miners in a former coal mining area. Subjects included 1,796 coal miners and 4,022 non-coal-miners, who were identified by a mail survey between 1987 and 1989, and then followed up from the date of the survey to April 30th, 1994. We applied Cox's proportional hazards model to compare the mortalities between coal miners and non-coal-miners. Among the coal miners, significantly high risk ratios were observed in all causes of death… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
12
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 14 publications
1
12
0
Order By: Relevance
“…The other factors are tobacco smoking (current, former, and currently not smoking), alcohol (current or currently not drinking), history of chronic gastric symptoms (yes or no), occupation (permanent or nonpermanent work), and coffee drinking (daily or occasionally). These factors control possible confounding factors (Haenszel et al, 1972;Hoey et al, 1981;Hisashige et al, 1983;Jeyaratnam et al, 1987;Kono et al, 1988;Yin et al, 1989;Hirayama, 1990;Kneller et al, 1990;Une et al, 1995;You et al, 1995;Galanis et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…The other factors are tobacco smoking (current, former, and currently not smoking), alcohol (current or currently not drinking), history of chronic gastric symptoms (yes or no), occupation (permanent or nonpermanent work), and coffee drinking (daily or occasionally). These factors control possible confounding factors (Haenszel et al, 1972;Hoey et al, 1981;Hisashige et al, 1983;Jeyaratnam et al, 1987;Kono et al, 1988;Yin et al, 1989;Hirayama, 1990;Kneller et al, 1990;Une et al, 1995;You et al, 1995;Galanis et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Several large cohort studies did not identify an increased lung cancer risk among coal miners either (15)(16)(17)(18). However, a prospective study in Japanese coal miners revealed an elevated smoking-adjusted risk of 2.4 for long-term mining (≥15 years) (14). Evidence of an association between exposure to quartz and lung cancer, but not with coal mine dust, was found in a large cohort of British coal miners (8), while an extended follow-up of a cohort of US coal miners reported an association with coal mine dust, but not with silica exposure (18), with the British cohort having a longer follow-up and a more robust exposure assessment (30).…”
Section: Discussionmentioning
confidence: 99%
“…Since then, epidemiological studies have reported mixed results on lung cancer among coal miners (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18), with extended follow-ups of cohort studies among British and US coal miners recently suggesting a positive association. However, exposure-specific results for coal dust and silica were not coherent between the two studies.…”
mentioning
confidence: 99%
“…Although coal miners are exposed to high concentrations of particulate from coal mine dust, studies which have examined the risk of ischemic heart disease (IHD) mortality among coal miners have had inconsistent results. Some have shown a risk no different, or lower than that of the general population [Rockette, 1977;Christie et al, 1995;Une et al, 1995], while others have shown increased risk, either overall, or among subgroups [Liddell, 1973;Costello et al, 1975;Atuhaire et al, 1986;Meijers et al, 1997;Attfield and Kuempel, 2008;Miller and MacCalman, 2010].…”
Section: Introductionmentioning
confidence: 99%